Export operation in Goodyear (M) Berhad / Roslina Tajuddin - Tajuddin, Roslina (1995)
The story begins in the year 1929, when the Goodyear Orient Sales Company was established in Singapore. As trading increased, a British Engineering Hard Ware Company, Kyle Palmer Limited was engaged to distribute Goodyear product in Malaya. Goodyear Malaysia first started with 15 employees and a monthly turnover of about 70 000 ringgit. In 1964, Goodyear Malaysia Private Limited was set up with its head office in Petaling Jaya. In the same year Goodyear entered into product off take arrangement under licence with Dunlop and Goodyear tyres made in Malaysia for the first time ever